2019
DOI: 10.1016/j.anl.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-associated lymphoproliferative disorder with multiple pulmonary nodules and bilateral cervical lymphadenopathy

Abstract: As has been well recognized, methotrexate (MTX) leads to a state of immunosuppression and can provide a basis for the development of lymphoproliferative disorders (LPDs). MTX-associated LPDs can affect nodal sites as well as extranodal sites, though the manifestation of an LPD in the form of multiple pulmonary nodules is rare. Here, we report two cases of MTX-associated LPD with multiple bilateral pulmonary nodules, which was a finding suggestive of lung cancer, and bilateral cervical lymphadenopathy. After wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The histologic patterns of MTX-LPD are heterogeneous; however, diffuse large B-cell lymphomais the most common histologic type (58%), followed by classical Hodgkin's lymphoma (15.3%) [3]. Some cases (25%, particularly the regressive group) could not be classified into a particular histologic type, because in these cases, MTX had already been discontinued and MTX-LPD was regressing at the time of biopsy [10]. Although it may be clinically difficult, a biopsy should be performed before MTX discontinuation, if possible.…”
Section: Discussionmentioning
confidence: 99%
“…The histologic patterns of MTX-LPD are heterogeneous; however, diffuse large B-cell lymphomais the most common histologic type (58%), followed by classical Hodgkin's lymphoma (15.3%) [3]. Some cases (25%, particularly the regressive group) could not be classified into a particular histologic type, because in these cases, MTX had already been discontinued and MTX-LPD was regressing at the time of biopsy [10]. Although it may be clinically difficult, a biopsy should be performed before MTX discontinuation, if possible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Makihara et al reviewed MTX-LPD cases with multiple pulmonary nodules. 18 In their review, imaging findings for pulmonary lesions of MTX-LPD, not limited by DLBCL-type LPD, were varied and included nodular density, infiltrative shadows, and ground-glass patterns. To the best of our knowledge, there are few reports regarding imaging-based prognostic factors for MTX-LPD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of onset is not fully understood, it is believed that the combination of immunodeficiency and the immunosuppressive effect of MTX has been implicated in the pathogenesis of MTX associated LPDs. The World Health Organization (WHO) has classified MTX associated LPDs as lymphoid neoplasms, whether iatrogenic or immunodeficiency associated diseases [ 73 , 75 ]. MTX associated LPDs often take a spontaneous remission, which tends to complete mostly within 4 weeks, after the discontinuation of MTX [ 74 ].…”
Section: The Side Effects Of Mtxmentioning
confidence: 99%
“…Moreover, a few studies have shown that long-term MTX use can lead to lymphoproliferative disorders (LPDs) in both nodal sites and extra nodal sites, such as the skin, lungs, epipharynx, thyroid gland, nasal cavity, spleen, and kidneys, especially for patients who are positive for EBV infection [70][71][72][73]. e reported frequency of EBV positive in MTX associated LPDs patients is 27%-50% [74].…”
Section: The Side Effects Of Mtxmentioning
confidence: 99%